The tangled cases of Deinogalerix (Late Miocene endemic erinaceid of Gargano) and Galericini (Eulipotyphla, Erinaceidae): a cladistic perspective. (12th September 2017) - Borrani, Antonio; Savorelli, Andrea; Masini, Federico; Mazza, Paul P. A.
Abstract: The Late Miocene giant erinaceid Deinogalerix from Scontrone and Gargano (Italy) is associated with many other vertebrates in deposits of a past island, the "Abruzzo‐Apulia Platform". At Gargano, Deinogalerix is accompanied by the moderately endemized Galericini Apulogalerix . This first extensive cladistic analysis is aimed at defining the relationships of Deinogalerix with characteristic members of the tribe Galericini. The analysis was performed on a matrix of 30 characters and 19 taxa and identified some smaller clades, nested within three major ones. The latter include: (i) a pentatomy of Galerix species, (ii) a polytomy of "transitional" Galerix – Parasorex species and (iii) a large clade with Parasorex, Schizogalerix and Gargano representatives. Galerix and Parasorex proved to be paraphyletic and Schizogalerix monophyletic. Based on the results of the analysis, Deinogalerix and Apulogalerix have distinct origins, which supports an asynchronous colonization of the island. The line of Deinogalerix possibly stemmed from some eastern species transitional between Galerix and Parasorex around Mammal Neogene (MN) zone 2. Conversely, the line of Apulogalerix originated from a primitive Parasorex ibericus, or a close relative, around MN 9–10. Another important result was detecting an impressive early Miocene (MN 2?) radiation of Galericini. Moreover, Schizogalerix and Parasorex originated from eastern Galericini morphologically transitional between Galerix and Parasorex .